2016
DOI: 10.1016/j.athoracsur.2016.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Repair of Recurrent Tracheoesophageal Fistula With an Atrial Septal Occluder Device

Abstract: A 32-year-old woman presented with recurrent trachea-esophageal fistula. Although she had undergone open repair three times in her first year of life, a residual small leak was left. In the past 2 years she had experienced several lower respiratory tract infections and she had lost 5 kilograms in the past 2 months. Recent argon plasma coagulation cauterization and clipping of the fistula had failed, so an alternative technique with placement of an atrial septal occluder device was used to obliterate the fistul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…[42][43][44][45][46][47][48] Li et al 42 conducted a case series on six patients with esophageal-respiratory fistulas (four benign and two malignant fistulas), used similar CSOs and a vessel plug (Lifetech Scientific Co., China), and presented a 100% immediate successful closure rate; however, four fistulas recanalized (two due to malignance). Two other studies 44,48 also used a similar ASD device (Gore, Flagstaff, AZ, USA) in patients with tracheoesophageal fistulas with successful closure. The AM-PLATZER TM vascular plug is indicated to embolize the vessels; however, similar with other septal occluders, it has been used for closure of GI fistula defects.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48] Li et al 42 conducted a case series on six patients with esophageal-respiratory fistulas (four benign and two malignant fistulas), used similar CSOs and a vessel plug (Lifetech Scientific Co., China), and presented a 100% immediate successful closure rate; however, four fistulas recanalized (two due to malignance). Two other studies 44,48 also used a similar ASD device (Gore, Flagstaff, AZ, USA) in patients with tracheoesophageal fistulas with successful closure. The AM-PLATZER TM vascular plug is indicated to embolize the vessels; however, similar with other septal occluders, it has been used for closure of GI fistula defects.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment requires a multidisciplinary approach and specific course of action differs case by case. Although several reports of primary endoscopic treatment of BEF were published, first-line treatment remains surgical repair which results in excellent long-term outcomes and should be performed as soon as possible after diagnosis [3, 4]. The timing of the surgery is also given by the patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery is associated with the adverse events, of which the most feared one is a recurrence of the fistula. Any subsequent open repair with thoracotomy is technically challenging and implies a high risk of complications [3]. The incidence of recurrence after the primary surgery based on limited data is up to 10% [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an alternative repair technique using an atrial septal occlude device has also been shown to be effective. 3 When a TE fistula is suspected but cannot be located on bronchoscopy, performing upper endoscopy is the next logical mandatory step. Careful observation of the esophagus during upper endoscopy is always advised not to miss any important lesions such as TE fistula.…”
Section: Answer To: Image 4 (Page 362): Balloon Cuff Of a Tracheostommentioning
confidence: 99%